Chimeric Antigen Receptor T Cell Therapies: A Review of Cellular Kinetic‐Pharmacodynamic Modeling Approaches. (17th November 2020) - Chaudhury, Anwesha; Zhu, Xu; Chu, Lulu; Goliaei, Ardeshir; June, Carl H.; Kearns, Jeffrey D.; Stein, Andrew M.
Abstract: Chimeric antigen receptor T cell (CAR‐T cell) therapies have shown significant efficacy in CD19+ leukemias and lymphomas. There remain many challenges and questions for improving next‐generation CAR‐T cell therapies, and mathematical modeling of CAR‐T cells may play a role in supporting further development. In this review, we introduce a mathematical modeling taxonomy for a set of relatively simple cellular kinetic‐pharmacodynamic models that describe the in vivo dynamics of CAR‐T cell and their interactions with cancer cells. We then discuss potential extensions of this model to include target binding, tumor distribution, cytokine‐release syndrome, immunophenotype differentiation, and genotypic heterogeneity.